2012
DOI: 10.1109/tdmr.2012.2194784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Stresses on Carrier Mobility and Keep-Out Zone Around Through-Silicon Vias for 3-D Integration

Abstract: Abstract-Three-dimensional (3-D) integration with throughsilicon vias (TSVs) has emerged as an effective solution to overcome the wiring limit imposed on device density and performance. However, thermal stresses induced in the TSV structures can affect the device performance by degrading carrier mobility and raise serious reliability concerns. In this paper, the effect of thermal stresses in TSV structures on carrier mobility and keep-out zone (KOZ) was investigated by focusing on the characteristics of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 25 publications
0
32
1
Order By: Relevance
“…(1) Figure 3: TSV structure [7] If Z S = Z 0 , that is; impedance of two-port input, no reflections occur and a 1 = 0. If Z L = Z 0 that is; the impedance of two-port output, no reflections occur and a 2 = 0.…”
Section: S-parametersmentioning
confidence: 99%
“…(1) Figure 3: TSV structure [7] If Z S = Z 0 , that is; impedance of two-port input, no reflections occur and a 1 = 0. If Z L = Z 0 that is; the impedance of two-port output, no reflections occur and a 2 = 0.…”
Section: S-parametersmentioning
confidence: 99%
“…The local plasticity is found to reduce the amount of mobility change and thus the size of the KOZ. More details of the KOZ study can be found in a separate publication [9].…”
Section: Residual Stress and Keep-out Zone (Koz)mentioning
confidence: 99%
“…Thermal stresses can arise during fabrication, testing and operation of the TSV structures due to the large mismatch in the coefficient of thermal expansion (CTE) between Cu and Si. The stresses are large enough to cause serious reliability concerns even structural failures in the integrated structure, including TSV extrusion, cracking of Si near the TSV and degradation of device performance [5][6][7][8][9]. Management and mitigation of thermal stresses in the TSV structures require proper stress characterization and modeling analysis.…”
Section: Introductionmentioning
confidence: 99%
“…And then, the carrier mobilities of pMOS and nMOS transistor channels would be affected. Keep-out zone (KOZ) is a common quantitative representation for the impact of thermal stress on transistors [7].…”
Section: Introductionmentioning
confidence: 99%